2022
DOI: 10.1007/s43681-022-00201-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the ethical and social concerns of artificial intelligence in neuroinformatics research: an empirical test of the European Union Assessment List for Trustworthy AI (ALTAI)

Abstract: Ethical and social concerns are a key obstacle to the adoption of artificial intelligence (AI) in the life sciences and beyond. The discussion of these issues has intensified in recent years and led to a number of approaches, tools and initiatives. Key amongst them is the idea of ex-ante impact assessments that aim to identify issues at the early stages of development. One prominent example of such ex-ante impact assessment is the European Union's (EU) Assessment list for Trustworthy AI (ALTAI). This article u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
(67 reference statements)
0
0
0
Order By: Relevance
“…SHAPES partners have acknowledged that the ALTAI tool is a reliable and easyto-use self-assessment tool for Trustworthy AI-based technology in pilot studies such as SHAPES pilots, which are of interest in the market. Similar analyses [11,12] have reported the importance of the ALTAI tool to provide reliable recommendations towards the improvement of trustworthiness in AI solutions. Specifically, although authors in [11] have slightly altered the ALTAI tool questions in their study, their results' analysis showed an awareness of some of the broader key areas of trustworthy factors as indicated by the ALTAI tool, such as accuracy of the performance of the AI solution.…”
Section: Lessons Learnedsupporting
confidence: 57%
See 2 more Smart Citations
“…SHAPES partners have acknowledged that the ALTAI tool is a reliable and easyto-use self-assessment tool for Trustworthy AI-based technology in pilot studies such as SHAPES pilots, which are of interest in the market. Similar analyses [11,12] have reported the importance of the ALTAI tool to provide reliable recommendations towards the improvement of trustworthiness in AI solutions. Specifically, although authors in [11] have slightly altered the ALTAI tool questions in their study, their results' analysis showed an awareness of some of the broader key areas of trustworthy factors as indicated by the ALTAI tool, such as accuracy of the performance of the AI solution.…”
Section: Lessons Learnedsupporting
confidence: 57%
“…Similar analyses [11,12] have reported the importance of the ALTAI tool to provide reliable recommendations towards the improvement of trustworthiness in AI solutions. Specifically, although authors in [11] have slightly altered the ALTAI tool questions in their study, their results' analysis showed an awareness of some of the broader key areas of trustworthy factors as indicated by the ALTAI tool, such as accuracy of the performance of the AI solution. Moreover, the study revealed that the participating researchers were unsure whether their work was covered by the various definitions and how applicable the recommendations could be to their solutions.…”
Section: Lessons Learnedsupporting
confidence: 57%
See 1 more Smart Citation
“…The societal impact of artificial intelligence (AI) has been a topic of increasing concern and scrutiny in recent years. Numerous studies have highlighted the ethical, legal, and socio-economic implications of AI deployment across various domains (Stahl, and Leach, 2023;Taeihagh, 2021). Ethically, AI systems raise concerns regarding bias, fairness, and accountability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, to help users to improve their understanding of the inherent risks of AI systems and to mitigate these risks, organizations and scholars have created several tools. For example, the European Commission created the Assessment List for Trustworthy AI (ALTAI) [22,23], which indicates self-assessment checklist questions and a set of steps that organizations are encouraged to complete. Each question presents multiple choices to verify the implementation of the guidelines.…”
Section: Human-ai Synergymentioning
confidence: 99%